Identification of short open reading frames in plant genomes - Feng, Yong; Jiang, Mengyun; Yu, Weichang; Zhou, Jiannan (Frontiers in Plant Science, 2023)
The roles of short/small open reading frames (sORFs) have been increasingly recognized in recent years due to the rapidly growing number of sORFs identified in various organisms due to the development and application of the Ribo-Seq technique, which sequences the ribosome-protected footprints (RPFs) of the translating mRNAs. However, special attention should be paid to RPFs used to identify sORFs in plants due to their small size (~30 nt) and the high complexity and repetitiveness of the plant genome, particularly for polyploidy species. In this work, we compare different approaches to the identification of plant sORFs, discuss the advantages and disadvantages of each method, and provide a guide for choosing different methods in plant sORF studies.